2021
DOI: 10.1542/hpeds.2020-005314
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Bacterial Respiratory Culture Results in Children With Neurologic Impairment

Abstract: OBJECTIVES To examine bacterial respiratory cultures in children with neurologic impairment (NI) (eg, cerebral palsy), both with and without tracheostomies, who were hospitalized with acute respiratory infections (ARIs) (eg, pneumonia) and to compare culture results across hospitals and age groups. METHODS This multicenter retrospective cohort study included ARI hospitalizations for children aged 1 to 18 years with NI between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
3
15
1
Order By: Relevance
“…42 On the other hand, children who are at risk for chronic P. aeruginosa due to immunocompromised status, comorbidities, or high hospital utilization are also likely at higher risk for mortality related to these non-pseudomonal factors, as has been reported in other populations. 37,[43][44][45][46][47] This study demonstrated a similar overall mortality rate to that reported in other studies of infants and young children with severe BPD and tracheostomies. 9 In survival analysis, we identified that most deaths occurred in the first 1 year following tracheostomy placement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…42 On the other hand, children who are at risk for chronic P. aeruginosa due to immunocompromised status, comorbidities, or high hospital utilization are also likely at higher risk for mortality related to these non-pseudomonal factors, as has been reported in other populations. 37,[43][44][45][46][47] This study demonstrated a similar overall mortality rate to that reported in other studies of infants and young children with severe BPD and tracheostomies. 9 In survival analysis, we identified that most deaths occurred in the first 1 year following tracheostomy placement.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, our center's results may not be generalizable to other institutions; our institution's positive culture prevalence is notably lower than that observed at other institutions, 20,50 but consistent with our prior internal studies. 21,44 This lower prevalence is hypothesized to be related to differences in our population and/or local factors (e.g., infection control policies, lab reporting procedures). Similarly, as noted above, the number of children meeting chronic P. aeruginosa identification criteria was very small which limits the conclusions from that subgroup's analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have demonstrated wide inter-institutional variability in culture ordering practices, microbiology lab processing, culture results (both positivity rate and organism type), and clinician response to results. 5,7,39 Variability in sample quality and lab processing may also contribute, as has been documented in endotracheal tube cultures. 39 The consequence of this variability is clinical inconsistency in diagnosing ARI, 5 use of and types of antibiotic treatment, 32 and probably also patient outcomes including severity, length of illness, and respiratory support needs, all of which limit research and improvement efforts.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although easy to order and obtain in children with tracheostomies, the interpretation of respiratory cultures is highly complex due to many confounding factors, which have largely been understudied. 7 A major contributor to the difficulty in interpreting culture results in this population is a lack of a robust epidemiologic understanding of organisms expected to be isolated during true ARI, let along during states of wellness. The respiratory tract, unlike other body compartments from which cultures are obtained (e.g., urine, blood), is not a sterile site and harbors oropharyngeal flora in children with and without tracheostomies.…”
Section: Introductionmentioning
confidence: 99%
“…There was a high abundance of Pseudomonas spp. at baseline that decreased afterward, which may be because of hospitalization and antibiotic use of premature infants ( Henares et al, 2021 ; Warniment et al, 2021 ). Common nosocomial genera, including Staphylococcus , Acinetobacter , and Pseudomonas, developed in infants subjected to antibiotics ( Henares et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%